Reversible Topochemical Exsolution of Iron in BaFe2+2(PO4)21. (24th October 2014) - David, Rénald; Kabbour, Houria; Filimonov, Dmitry; Huvé, Marielle; Pautrat, Alain; Mentré, Olivier
Abstract BaFe2+2(PO4)2 was recently prepared and identified as the first 2D‐Ising ferromagnetic oxide with an original reentrant structural transition driven by high‐spin Fe2+ ions arranged in honeycomb layers. Both long‐term air exposure and moderate temperature (T>375 °C) leads to topochemical oxidation into iron‐depleted compounds with mixed Fe2+/Fe3+ valence. This process is unique, as the exsolution is effective even from single crystal with preservation of the initial crystallinity, and the structure of the deficient BaFe2−x(PO4)2 (x<ca. 0.5) is fully ordered for x=2/7 and 1/3 with creation of novel original depleted triangular lattices. Under flowing H2/Ar, Fe is reincorporated in the structure above 480 °C, as reproduced under the electron beam in a transmission microscope. After Fe exsolution, the insulating ferromagnetic compound turns into an antiferromagnetic semiconductor.